Neurobebavioural effects of long-term exposure to organophosphates in tobacco-growing farmers in Kelantan - Nordin, Rusli; Musa, Razlan; Kyi, Daw Win; Ismail, Hasanah Che (2001)
In order to investigate the neurobehavioural effects in workers chronically exposed to organophosphate pesticides in Malaysia using the WHO neurobehavioural core test battery (NCTB), a cross-sectional study of 45 organophosphate-exposed tobacco-growing farmers and 45 controls was conducted. Seven tests of the NCTB profile of mood states,simple reaction time,digit symbol,digit span, Santa Ana manual dexterity,Benton visual retention, and pursuit aiming tests were administered to the subjects.The mean serum cholinesterase activity in organophosphate-exposed farmers (8924.7 IU/1) was significantly different from controls (116421.4 IU/1) but within normal range (5300 to 12900 IU/1).The results of analysis of covariance,in which age, length of education, and duration of employment, (covariates) were controlled in 45 exposed farmers and 45 controls, showed that the mean scores on the Profile of mood states-vigour (POMSvigour),digit symbol correct,digit span forward and digit span backward, Santa Ana non-preferred hand,Benton visual retention test and pursuit aiming tests were significantly lower in the exposed farmers than controls. The results of stepwise multiple regression analysis revealed that none of the neurobehavioural tests score for 45 organophosphates-exposed farmers were significantly related to serum cholinesterase (Pearson's product-moment correlation [p>0.05]).However,scores on the digit symbol correct, digit span backward and pursuit aiming tests were significantly related to length of education.We therefore conclude that chronic effects on the nervous system have occurred in this group of farmers and that these effects are likely to be associated with long-term repeated exposure to organophosphate pesticides.